The Impact of Innovation Capability on Product Innovation Performance (Case Study of Manufacturing Industry in Indonesia) - Agatha Hintama; Mira Maulida; Yosman Bustaman (ADI Publisher, 2020)
Manufacturing industry contributes the highest to Indonesian’s GDP, but it continues to slide from 2015-2018 due to low number of new products and low diversification products. Thus, this study focuses on the capability in enhancing product innovation performance. Capabilities relate to RBV (resource-based view) of a firm. It explains how firms renew their competencies in order to adapt to the changing environment. In analysing the relation between innovation capability and product innovation performance, this study also considers the role of R&D performance. Many studies mentioned that innovation capability impacts R&D performance and product innovation performance. But there is still limited study that explores innovation capability as a moderating role towards R&D performance and product innovation performance. This study uses Structural Equation Method (SEM) which consist of 100 respondents of senior management in the manufacturing industry in Indonesia. Our study shows that innovation capability enhances product innovation performance better through R&D performance; rather than direct relation. But innovation capability has no moderating role towards the relation of R&D performance and product innovation performance.